2016
DOI: 10.1016/j.ress.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Warranty menu design for a two-dimensional warranty

Abstract: a b s t r a c tFierce competitions in the commercial product market have forced manufacturers to provide customerfriendly warranties with a view to achieving higher customer satisfaction and increasing the market share. This study proposes a strategy that offers customers a two-dimensional warranty menu with a number of warranty choices, called a flexible warranty policy. We investigate the design of a flexible twodimensional warranty policy that contains a number of rectangular regions. This warranty policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…That is, the warranty only covers one dimension, which can be either the usage or the age dimension, but not both. For some products (see Ye and Murthy (2016), for example), however, a warranty policy may cover both age and usage (e.g., the warranty of a car may cover both age and mileage), which is called a two-dimensional warranty policy. Our future work aims to investigate the optimisation problem for products with a two-dimensional warranty coverage.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the warranty only covers one dimension, which can be either the usage or the age dimension, but not both. For some products (see Ye and Murthy (2016), for example), however, a warranty policy may cover both age and usage (e.g., the warranty of a car may cover both age and mileage), which is called a two-dimensional warranty policy. Our future work aims to investigate the optimisation problem for products with a two-dimensional warranty coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Using the proposed equations, we can calculate the cost in each subinterval (see Table 7 for details). Manufacturers can hardly predict the usage rate of consumers when products are sold, which has been observed in our previous studies and other works (Ye and Murthy 2016) [36]. Meanwhile, minimal repair is the most commonly used in the actual operation of base warranty period.…”
Section: Mathematical Model Of Two-dimensional Lifetime Warranty Stramentioning
confidence: 81%
“…However, the increasing strict warranty service content has brought a huge warranty cost pressure to manufacturers (Huang et al 2015 [11]; Su and Wang 2016 [28]; Wang and Su 2016 [32]; Wang et al 2015 [33]), and the warranty cost can range from 2% to 15% of the net sales (Murthy and Djamaludin 2002). To reduce the warranty cost borne by manufacturers, many scholars have formulated maintenance models under one-and two-dimensional warranty (see details in Banerjee and Bhattacharjee 2012 [2]; Chien 2012 [6]; Huang et al 2013 [10]; Khojandi et al 2014 [15]; Lin and Yeh 2010 [17]; Shang et al 2016 [26]; Varnosafaderani and Chukova 2012 [31]; Ye and Murthy 2016 [36]). Generally, previous studies have considered age as the variable of one-dimensional warranty and adopted age and usage as the variables of two-dimensional warranty, except for Park et al (2017) [22] who considered failure time and repair time as variables.…”
mentioning
confidence: 99%
“…Through the aforementioned literature review, it can be found that warranty service providers usually provide homogeneous warranty service to consumers, including service coverage, maintenance strategy and service price. Considering the differences of consumers' usage habits, some literatures have studied the differentiated maintenance strategies (Ye and Murthy 2016) [36], service pricing (Tong et al 2014) [29], claim behaviour (Gallego et al 2015) [5] and warranty cost analysis (Huang et al 2015) [7]in recent years. However, there are few studies have focused on differentiated warranty coverage that considers usage rate and service option of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The interval of usage rate intensityTong et al 2014[29];Wang et al 2015[34]; Ye and Murthy 2016[36]). However, a partial overlap is observed in the boundaries of the usage rate intervals under this classification criterion.…”
mentioning
confidence: 99%